The in vivo dsRNA Cleavage Has Sequence Preference in Insects - Guan, Ruobing; Hu, Shaoru; Li, Haichao; Shi, Zhenying; Miao, Xuexia (Frontiers in Physiology, 2018)
Exogenous dsRNA enters the insect body and can induce the RNAi effect only when it is cleaved into siRNA. However, what kinds of base composition are easier to cut and what kinds of siRNA will be produced in vivo is largely unknown. In this study, we found that dsRNA processing into siRNA has sequence preference and regularity in insects. We injected 0.04 mg/g dsRNA into Asian corn borers or cotton bollworms according to their body weight, and then the siRNAs produced in vivo were analyzed by RNA-Seq. We discovered that a large number of siRNAs were produced with GGU nucleotide residues at the 5′- and 3′-ends and produced a siRNA peak on the sequence. Once the GGU site is mutated, the number of siRNAs will decrease significantly and the siRNA peak will also lost. However, in the red flour beetle, a member of Coleoptera, dsRNA was cut at more diverse sites, such as AAG, GUG, and GUU; more importantly, these enzyme restriction sites have a high conservation base of A/U. Our discovery regarding dsRNA in vivo cleavage preference and regularity will help us understand the RNAi mechanism and its application.